2009
DOI: 10.1371/journal.pone.0004330
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Improves Cognitive Responses to Psychological Stress through Enhancement of Epigenetic Mechanisms and Gene Expression in the Dentate Gyrus

Abstract: BackgroundWe have shown previously that exercise benefits stress resistance and stress coping capabilities. Furthermore, we reported recently that epigenetic changes related to gene transcription are involved in memory formation of stressful events. In view of the enhanced coping capabilities in exercised subjects we investigated epigenetic, gene expression and behavioral changes in 4-weeks voluntarily exercised rats.Methodology/Principal FindingsExercised and control rats coped differently when exposed to a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(84 citation statements)
references
References 50 publications
2
79
2
1
Order By: Relevance
“…S2 A and B). The ventral blade neurons were not affected by the stressor (as shown previously) (5,19,20) or SAM treatment. The effect of SAM was unique to the DG because stress-induced c-Fos and Egr-1 expression in the CA1 and CA3 regions of the hippocampus was unaffected by the injected methyl donor (Fig.…”
Section: Sam Impairs Consolidation Of Fs-induced Behavioral Responsessupporting
confidence: 79%
“…S2 A and B). The ventral blade neurons were not affected by the stressor (as shown previously) (5,19,20) or SAM treatment. The effect of SAM was unique to the DG because stress-induced c-Fos and Egr-1 expression in the CA1 and CA3 regions of the hippocampus was unaffected by the injected methyl donor (Fig.…”
Section: Sam Impairs Consolidation Of Fs-induced Behavioral Responsessupporting
confidence: 79%
“…Any abrogation in H3S10p-K14ac and c-Fos formation in these neurons due to NMDA receptor or GR antagonism, MEK (MAPK kinase) inhibition (i.e., prevention of ERK activation), or double genetic deletion of MSK1/2 resulted in an impairment of memory formation. 19,20,35 Moreover, recently we demonstrated that exercising rats show enhanced H3S10p-K14ac and c-Fos responses in their dentate gyrus to forced swimming (and novelty) as well as a better memory performance of the event than their sedentary counterparts 49 which may be due to enhanced GR function in these animals. 50,51 Preliminary data provided evidence for a role of H3S10p-K14ac and c-Fos induction in dentate neurons in Morris water maze learning ERK MAPK pathway.…”
Section: Significance Of H3s10p-k14ac-driven Gene Expression In Dentamentioning
confidence: 89%
“…Previous studies have shown changes in covalent histone modification in a variety of models, including seizures (35), psychostimulant treatment (36), exercise (37), and depression (13,38). Epigenetic mechanisms are now thought to be potential contributors both to normal cognitive processes and to a variety of neuropsychiatric diseases (7,9,39).…”
Section: Discussionmentioning
confidence: 99%